KAJIAN TATA KELOLA KEUANGAN GEREJA - Sihombing, Tombek Robert Tua (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
The church as a gathering place for believers certainly has a purpose in its ministry. as a non-profit organization that gets its financial resources from the congregation, of course, it certainly has no responsibility to make a profit. Servants as church administrators who work voluntarily are certainly not always required to be professional. Because church servants are people chosen by God to serve in the church based on a calling. Therefore, the role of church governance is not an absolute guide. The method used in this research is a literature study that obtains data from various sources on the internet, books or other media. The data obtained in this study were 15 sources consisting of 13 journals on governance, books and 1 HKI church household regulations. The result of the research is that not all churches apply the principles of good governance. The principles of transparency and accountability are principles that often appear in various church governance journals. Calls to transfer governance by applying the principles of good governance are urgently needed, therefore assistance to churches in making good governance is also required.